2022
DOI: 10.1002/imhj.21970
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life in home visitors: Core components of the reflective supervisory relationship and IMH‐E® Endorsement® engagement

Abstract: Infant and early childhood home visiting models are gaining prominence as effective programs for families. Most U.S. state infant mental health associations (IMHAs) recommend reflective supervision (RS) and Infant Mental Health (IMH‐E®) Endorsement® as components of home visitor professional development. These efforts may promote workforce professional quality of life. It is unknown whether a workplace policy to provide RS improves the likelihood that best practice guidelines, especially core components of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Although results from these studies are heterogenous, there is some evidence to suggest receiving RS/C may be positively associated with well‐being and negatively associated with secondary traumatic stress, burnout, and related constructs. For instance, two cross‐sectional studies found that experiencing a high‐quality reflective supervision relationship was associated with lower levels of secondary traumatic stress and burnout (Begic et al., 2019; Eaves et al., 2022), lower levels of intention to quit (Begic et al., 2019), and higher levels of compassion satisfaction (Eaves et al., 2022) among home visitors. In a cross‐sectional study of providers spanning many early childhood settings, those who had received no reflective supervision reported higher levels of internalizing symptoms compared to providers who had received at least one year of reflective supervision (Morelen et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although results from these studies are heterogenous, there is some evidence to suggest receiving RS/C may be positively associated with well‐being and negatively associated with secondary traumatic stress, burnout, and related constructs. For instance, two cross‐sectional studies found that experiencing a high‐quality reflective supervision relationship was associated with lower levels of secondary traumatic stress and burnout (Begic et al., 2019; Eaves et al., 2022), lower levels of intention to quit (Begic et al., 2019), and higher levels of compassion satisfaction (Eaves et al., 2022) among home visitors. In a cross‐sectional study of providers spanning many early childhood settings, those who had received no reflective supervision reported higher levels of internalizing symptoms compared to providers who had received at least one year of reflective supervision (Morelen et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Eaves et al (2022) provided more nuance to this finding. They found that having a workplace policy supporting the provision of reflective supervision was not directly related to secondary traumatic stress, burnout, or compassion satisfaction in home visitors; however, having a workplace policy was associated with more consistently experiencing core components of a reflective supervisory relationship, which in turn was associated with each of these outcomes (Eaves et al, 2022). Interestingly, participants who reported higher quality reflective supervision and spent more time in group supervision perceived their workplace as having a better learning culture (Julien-Chinn & Lietz, 2019), suggesting a possible bidirectional effect of reflective supervision and workplace culture.…”
Section: Barriers and Facilitators Affecting Implementation Of Rs/cmentioning
confidence: 94%
See 3 more Smart Citations